Hubungan Perilaku Merokok Dengan Kejadian TB Paru pada Perokok Aktif di Puskesmas Telaga Dewa Kota Bengkulu Tahun 2025 - Undal Rhomadhon Sulystyo Pambudi; Tita Septi Handayani; Nuche Marlianto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Pulmonary tuberculosis (TB) is an infectious communicable disease that remains a public health problem, including in Bengkulu City. One behavioral factor suspected to contribute to the incidence of pulmonary TB is smoking behavior. This study aimed to examine the association between smoking behavior and the occurrence of pulmonary TB among active smokers at Telaga Dewa Community Health Center, Bengkulu City, in 2025.This study employed a quantitative design with a case–control approach. The study population comprised all visitors aged over 15 years registered at Telaga Dewa Community Health Center, Bengkulu City. A total of 66 respondents were selected using purposive sampling. The research instruments included a smoking behavior questionnaire and data on pulmonary TB incidence based on medical diagnoses. Data analysis was conducted using univariate and bivariate analyses, with the Chi-square test applied at a significance level of α = 0.05. The results showed that the majority of respondents exhibited heavy smoking behavior (33.3%), and more than half of the respondents had pulmonary TB (54.5%). The Chi-square test yielded a p-value of 0.021 (≤ 0.05), indicating a statistically significant association between smoking behavior and the incidence of pulmonary TB among active smokers at Telaga Dewa Community Health Center, Bengkulu City. The study concludes that there is a significant relationship between smoking behavior and the occurrence of pulmonary TB among active smokers. It is recommended that the community health center strengthen health education regarding the dangers of smoking and implement pulmonary TB prevention efforts through the promotion of healthy lifestyle behaviors.